Skeletal Bone Atrophy - Radiological Considerations - Babić, Rade R.; Mladenović, Marko; Stanković Babić, Gordana; Babić, Strahinja; Babić, Katarina; Babić, Nevena; Jevremović, Aleksandar (Medical Word, 2026)
Bone atrophy is a process of a qualitative nature, which occurs due to the weakened function of osteoblasts, while the function of osteoclasts is preserved. The work aims to draw attention to the fact that bone atrophy is a relevant elemental process in various pathological bone conditions and one of the signs of an atrophic complex, while the material of the work consists of selected roentgenogram from our own film library with bone atrophy acquired over many years of work in the profession. Through some characteristic pathological conditions and through illustrations, we show the atrophy of the bones of the skeleton. Conclusion: Skeletal bone atrophy is one of the relevant X-ray signs of skeletal bone disease by which elementary processes in bones are read, and combined into sets, symptom complexes or syndromes, which are sometimes more and sometimes less characteristic of certain diseases. In the radiological diagnosis of atrophy of the bone-joint system of the skeleton, the knowledge of radiologists and orthopedists is of relevant importance.